1999
DOI: 10.1046/j.1365-2648.1999.00861.x
|View full text |Cite
|
Sign up to set email alerts
|

Shift work and its impact upon nurse performance: current knowledge and research issues

Abstract: Previous research investigating shift work and its impact upon the quality of registered nurse performance and outcomes (including biological, psychosocial and organizational) is reviewed. The present study, which involved non-participant observation of staff nurses (n = 34) within their first year of practice (Part 1 or Part 12 of the United Kingdom Professional Register), is described. The findings demonstrated support for earlier research which suggested that 12 1/2 hour shifts are associated with less effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1
9

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 39 publications
(64 reference statements)
1
47
1
9
Order By: Relevance
“…In fact, nursing literature reports ambivalence about the benefits of this work shift pattern (Todd, Robinson, & Reid, 1993, p. 215). For example, Fitzpatrick, While, and Roberts (1999), Gillespie and Curzio (1996), and Northcott and Facey (1995) found that there was limited empirical evidence available to examine the impact this change has had on a myriad of variables.…”
Section: List O F Tablesmentioning
confidence: 99%
“…In fact, nursing literature reports ambivalence about the benefits of this work shift pattern (Todd, Robinson, & Reid, 1993, p. 215). For example, Fitzpatrick, While, and Roberts (1999), Gillespie and Curzio (1996), and Northcott and Facey (1995) found that there was limited empirical evidence available to examine the impact this change has had on a myriad of variables.…”
Section: List O F Tablesmentioning
confidence: 99%
“…Häkkänen e Summala (2000) constataram prevalência de 13% e shift workers entre os caminhoneiros que faziam viagens de longa duração, sendo que 40% desses referiram problemas em permanecer alerta. Outras profissões sofrem, da mesma forma e em demasia, com as mudanças do horário de trabalho, principalmente quando os turnos são alternados, como, por exemplo, policiais (Garbarino, 2002) e enfermeiros (Ferreira, 1985;Fitzpatrick et al, 1999;Gupta e Pati, 1994;Matsumoto et al, 1996). Outros pesquisadores comprovam o mesmo fato (Akerstedt e Torsvall, 1978;Bobko, 1994;Campbell, 1995;D'Alonzo Krachman, 2000;Gordon et al, 1986;Guimarães e Teixeira, 2003;Kan e Kupriianov, 1989;Mazzetti di Pietralata et al, 1990 …”
Section: Discussionunclassified
“…Udowodniono w licznych badaniach zwią-zek wydajności pracy z cechami osobowymi pracownika, pracą zmianową, poziomem stresu, wsparciem społecznym, relacjami interpersonalnymi, przywództwem, a także kulturą organizacyjną [18,20,21,22].…”
Section: Przegląd Badań Nad Wydajnością Pracy Pielęgniarekunclassified
“…Wyniki badania wykazały, że wyższe wartości sprawności fizycznej, a także sprawowania profesjonalnej opieki uzyskały pielęgniarki zatrudnione w systemie 8-godzinnym. Badacze wykazali, że 12-12,5-godzinne zmiany robocze związane są z obniżeniem poziomu wydajności pracy pielęgniarek [20]. Japońcy naukowcy Y. Fujino i R. Kawamoto podjęli próbę badawczą mającą na celu ocenę wpływu wykorzystywanej technologii informacyjnej i komunikacyjnej (ICT) na wydajność pracy pielęgniarek.…”
unclassified